Perceived Factors Influencing Postpartum Weight Gain among Nursing Mothers Attending Postnatal Clinic at Lagos State University Teaching Hospital, Ikeja, Lagos, Nigeria (IPS Journal of Public Health, 2024)
This research was carried out to assess the factors influencing postpartum weight gain among nursing mothers attending Post-natal Clinic at Lagos State University Teaching Hospital, Ikeja. Three objectives guided the study which were to identify the factors influencing postpartum weight gain, to assess the perception and attitude towards postpartum weight gain among the nursing mothers. A cross-sectional research design was adopted for the study, in which only one hundred and eighty-eight (188) of them met the inclusion criteria. Questionnaire was the instrument for data collection, data was analyzed using SPSS version 25, and presented on frequency percentage tables. Findings from the study revealed that the perceived factors influencing weight gain after childbirth among nursing mothers was mainly post-natal in nature; due to the use of family planning method 109(57.8%); followed by the consumption of fast food 93(49.3%); and inadequate physical exercise 66(35.2%) as the main factors. Their perceptions towards postpartum weight gain was majorly poor as 139(73.9%) of them affirmed that there is satisfaction with their present weight. An evaluation of their attitude towards weight gain after childbirth revealed an overall negative attitude towards the concept, as majority 132(70.4%) of them agreed that family planning can cause nursing mothers’ weight gain; about half 95(50.7%) of them attested to exercise being necessary after delivery to maintain healthy weight among nursing mothers. The study found a significant relationship between the perception and attitude of nursing mothers towards postpartum weight gain (r = .863; p < .05). Based on these findings, the study concluded that there is an urgent need to positively improve nursing mothers’ perception in order to improve their attitude towards weight gain after birth, through ante-natal health education, sensitization programmes and community mobilization addressing factors negatively influencing mothers’ perception and attitude towards postpartum weight gain especially during the ante-natal period.
Keywords: Postpartum weight gain; Nursing mothers; Perception and attitude; Factors